Sexual Minorities in Faith-Based Higher Education: A National Survey of Attitudes, Milestones, Identity, and Religiosity. Issue 1 (March 2013) - Stratton, Stephen P.; Dean, Janet B.; Yarhouse, Mark A.; Lastoria, Michael D.
Studies on faith-based campuses are beginning to offer a glimpse into the real experience of sexual minority students in these unique settings. This study adds to this growing body of information by surveying 247 undergraduates, who describe themselves as sexual minorities at 19 Christian schools across the United States. They responded to questions related to attitudes regarding sexuality, sexual identity, religiosity, and sexual milestone events. The results from this sample suggest those who attend higher education at faith-based institutions are a distinctive group within Western culture when it comes to the development of religious/spiritual identity and sexual identity. Although diversity with regard to same-sex and opposite-sex attraction is present among those surveyed, common themes exist for this unique sample of undergraduates. Implications for mainstream culture and Christian educational institutions are discussed.